Analysis of ferromanganese deposits from the Northwestern Pacific seamounts - Masato Joshima; Akira Usui (PANGAEA, 1998)
Fine-scale dating is crucial to understanding the growth and environments of formation of marine manganese deposits. The paleomagnetic method of dating of manganese nodules and crusts has been attempted but with no success so far. We measured remanent magnetization (RM) on up to 75-mm-thick hydrogenetic crusts at intervals of 2.5 mm after mineralogical and chemical examination, careful separation, and alternative field demagnetization. Stable sharp RM and well-correlated polarity-change patterns between four samples made it possible to identify the Pliocene-Quaternary magnetic chrons in them. These data show that the three crusts have grown continuously at rates of 14-17 mm/m.y. since the Early Pliocene. This is three or four times faster than those for Central Pacific seamount hydrogenetic crusts. Estimates of growth rate based on determination of Co-flux are within this range. Magnetostratigraphy therefore appears to be a powerful method for dating hydrogenetic manganese crusts when supported by conventional dating methods. These results encourage finer-scale investigations which promise more detailed paleoceanographic reconstruction.
Supplement to: Joshima, M; Usui, A (1998): Magnetostratigraphy of hydrogenetic manganese crusts from Northwestern Pacific seamounts. Marine Geology, 146(1-4), 53-62, https://doi.org/10.1016/S0025-3227(97)00131-X